(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
This article aims to expose the natural, cultural and patrimonial resources that Canton Salitre enjoys; and, from the scenario of these resources, actions framed in its culture and heritage are proposed, adding environmental strategies; that, the native entrepreneurs of the canton must take advantage of to attract real and potential own, local, regional and even national tourists through a plan of action and by the conditions tourism is potentiated. Entrepreneurs today have the task of integrating the natural, cultural and heritage resources of the place with the austere economic resources available to this group of entrepreneurs, to make their businesses attractive and seductive to tourists. For this purpose, a quantitative methodology was applied, applying a quantitative study on a real data of 50 entrepreneurs with more permanence in the canton, including a field observation, as well as a focus group, where they identified and valued the natural wealth, in addition to a survey in Google Forms directed to random visitors in field visit. The results that were achieved were of great interest since the natural inventory, customs and heritage of Cantón Salitre were recognized and enhanced, supported by the current government. From this study, an action plan is proposed in the short term, from which criteria and characteristics associated with the social and economic progress of the canton are derived.